OPTIMASI FORMULA PAKAN SAPI PERAH DENGAN LINIER PROGRAMMING UNTUK MINIMASI BIAYA BAHAN BAKU DI KOPERASI XYZ JAWA TENGAH - Sazli Tutur Risyahadi (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Formulation dairy feed of XYZ cooperative is still trial and error process and it can influence high material cost and unable to meet standard quality. This research has conducted to optimize the formula with Linear Programming so cooperative able to gain minimum material cost and achieves the standard requirements. The steps of formulation are identification minimal objective and determine the constraints functions to represent standard dairy nutrient including dry mater requirement (BK), crude protein (PK), Crude Fat (LK), Total Digestible nutrient (TDN), Calsium and Pospor. Optimization was calculated by using linear programming approach. Software used was solver contained in MS Excel. Optimization result show that The most feasible feed formulation used for product SP132 30% of bran, 31.7 of cassva pile., 13.7% of palm kernel meal, 6.02% of Hi Pro, 8.32% peanut shell , 7% molasess and 3% Slaz and for SP134 20% of bran, 37% of cassva pile., 2% Golden pro, 10% of Hi Pro, 7% coffee shell, 6% Peanut Shell, 15% molasess and 3% Slaz. This optimization can also reduce cost for SP 132 from 2500 rupiah to 1948 rupiah and for SP134 from 2800 rupiah to 2682 rupiah. Based on optimization result, there were cost reduction and improvement of dairy cattle ration quality